The effects of pre-school attendance on the cognitive development of urban children aged 5 and 8 years - Woldehanna, T; Gebremedhin, L (Young Lives, 2012)
This paper, using data from the Young Lives longitudinal survey in Ethiopia, examines the effects of pre-school attendance on the cognitive development of urban children at the ages of 5 and 8 (measured by the Peabody Picture Vocabulary Test (PPVT) and the Cognitive Development Assessment – Quantitative test (CDA-Q)). We used propensity score matching techniques in order to estimate the impact of pre-school. We also substantiated the analysis using various empirical approaches including ordinary least squares and instrumental variable estimation methods. Our results show that pre-school attendance has a statistically significant positive impact on the cognitive development of children at the ages of both 5 and 8 years, with the bigger impact at the latter age. Moreover, pre-school attendance has also a positive and statistically significant effect on primary school enrolment and progression through grades. Despite the fact that early childhood education has immense importance for children’s cognitive development, public investment in pre-school education is currently limited in Ethiopia, with the private sector taking the key role, which may exacerbate the inequality that exists between rich and poor (and between urban and rural areas). Therefore, given the relatively low rate of pre-school attendance and the low quality of basic education, the Government needs to reconsider its education priorities so as to invest more in early childhood education.